Influence Workload and Physical Work Environment on Job Satisfaction at PT Matahari Silverindo Jaya Semarang City - Milati Puja; Dody Setyadi; Sugiyanta (JOBS (Jurnal Of Business Studies), 2024)
Job satisfaction is something that must be considered by a company regarding optimizing employee performance. This study aims to analyze the influence of workload and physical work environment on job satisfaction. The data collection methods used were questionnaires and observation. The sample used was 100 production employees of PT Matahari Silverindo Jaya, Semarang City, with the data collection method, namely non-probability sampling. The analytical method applied in this study is multiple linear regression analysis with analytical methods in the form of determinant coefficient test, partial test (t test), and f test with the IBM SPSS 26 program. The results of data processing show that workload partially has a significant effect on job satisfaction while physical The work environment partially has a significant effect on job satisfaction. Meanwhile, for these two variables, workload and physical work environment can simultaneously have a significant effect on job satisfaction, namely 47%, the rest of which is influenced by other variables. Kepuasan kerja suatu hal yang mesti diperhatikan oleh perusahaan perihal mengoptimalkan kinerja karyawan, studi ini bermaksud menganalisis pengaruh workload dan physical work environment terhadap job satisfaction. Metode pengumpulan data yang dipakai ialah angket dan observasi. Sampel yang digunakan sebanyak 100 karyawan produksi PT Matahari Silverindo Jaya Kota Semarang, dengan motode pengambilan data yaitu non-probability sampling. Metode analisis diterapkan pada studi ini ialah analisis regresi linear berganda dengan metode analisis berupa uji koefisien determinan, uji parsial (uji t), dan uji f dengan program IBM SPSS 26. Hasil pengolahan data menunjukan bahwa workload secara parsial berpengaruh signifikan terhadap job satisfaction sedangkan physical work environment secar parsial berpengaruh signifikan terhadap job satisfaction. Sedangkan untuk kedua variabel ini workload dan physical work environment dapat berpengaruh signifikan secara silmutan terhadap job satisfaction ialah 47% yang dimana sisanya dipengaruhi oleh variabel lainnya.